2012
DOI: 10.1002/esp.3335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of helical flow in one‐dimensional modelling of sediment distribution at river bifurcations

Abstract: Complex flow processes at river bifurcations and the influence of the layout of a bifurcation make it difficult to predict sediment distribution over the downstream branches in case bedload transport dominates. In one‐dimensional models we need a nodal point relationship that prescribes the distribution of sediment over the downstream branches. We have identified which factors need to be included in such a relationship for the division of bedload transport at bifurcations. Next, irrotational flow theory for id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…In particular, he found a more frequent occurrence of branch abandonment for branches with a larger bifurcation angle deviation from the upstream branch. Although flume experiments of Federici and Seminara [2003] and numerical modeling by Van der Mark and Mosselman [2012] indicated no correlation between bifurcation angle asymmetry and bifurcation evolution, it is a plausible correlation and deserves further investigation. Furthermore, Koomen [1992], Ashworth et al [2000] and Schuurman et al [2013] found that the relative length of bar-tail limbs is an indicator of bifurcation asymmetry, and thus shortterm evolution: the dominant channel creates the longest bar-tail limb.…”
Section: Introductionmentioning
confidence: 91%
“…In particular, he found a more frequent occurrence of branch abandonment for branches with a larger bifurcation angle deviation from the upstream branch. Although flume experiments of Federici and Seminara [2003] and numerical modeling by Van der Mark and Mosselman [2012] indicated no correlation between bifurcation angle asymmetry and bifurcation evolution, it is a plausible correlation and deserves further investigation. Furthermore, Koomen [1992], Ashworth et al [2000] and Schuurman et al [2013] found that the relative length of bar-tail limbs is an indicator of bifurcation asymmetry, and thus shortterm evolution: the dominant channel creates the longest bar-tail limb.…”
Section: Introductionmentioning
confidence: 91%
“…First, we used Delft3D to systematically test scenarios. Delft3D is a physicsbased numerical model and simulates hydrodynamics, sediment transport, and morphodynamics and has been used in several fluvial, estuarine, deltaic, and tidal applications (e.g., Lesser et al, 2004;Edmonds and Slingerland, 2008;Kleinhans et al, 2008Kleinhans et al, , 2010van der Wegen and Roelvink, 2012;Schuurman et al, 2013) and is extensively used and verified in engineering practice. The model schematisation was inspired by the River Allier.…”
Section: Numerical Modelling Approachmentioning
confidence: 99%
“…So, the effects of helical flow driven by flow curvature on bed shear-stress direction were parameterized (Struiksma et al, 1985). Computation of morphodynamics included sediment transport induced by the flow and the longitudinal and transverse bed slope (Struiksma et al, 1985;Lesser et al, 2004;Kleinhans et al, 2008), bank erosion (van der Wegen and Roelvink, 2012), and bed level change because of gradients in sediment transport. Sediment transport was predicted by the Engelund and Hansen (1967) equation . At the inflow boundary, the input of sediment was kept equal to the local sediment transport capacity.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this special edition flow structures have been investigated in a simple configuration of a bifurcation through either the application of a physical scale model (Thomas et al, 2011) or through a full three-dimensional (3D) flow model utilizing a parametric study of how flow structures and partitioning are dependent upon geometric characteristics bifurcation . The effect of the predicted helical flow is considered by Van der Mark and Mosselman (2012) who develop a semi-analytical relationship for nodal points in a 1D framework to account for bedload sediment division due to the flow curvature at bifurcations and offtakes. However, these bifurcations consider immobile, smooth boundaries which will not represent natural features including inlet steps or bed ramps.…”
mentioning
confidence: 99%